La acción de Habeas Corpus como medio para garantizar el derecho a la libertad (2018)
In the year 1991, when our Magna Letter was promulgated, it was observed when carrying out its analysis that constitutional actions were assigned for the protection of rights, corporations, values and principles that would take the country through its judicial employees to a prompt, truthful and straight justice, which would prevent judicial congestion and therefore possible overcrowding; After 27 years since its entry into force, it can be seen that the courts and prosecutors' offices are full of unresolved trials and therefore prison centers full of prisoners whose legal situation could in the most favorable of cases be defined in years, it is at this point that it is perceived that the writ of habeas corpus, being this constitutional and of immediate application, is not being administered in due form, thus going against the fundamental rights set forth in the maximum standard